Chemical enhanced oil recovery: synergetic mechanism of alkali, surfactant and polymer with overview of methyl ester sulfonate as a green alternative for EOR surfactant - Habib, Saiful Hafiz; Yunus, Robiah; Zakaria, Rabitah; Awang Biak, Dayang Radiah; Mohamed Jan, Badrul Hisham; Amir, Zulhemi (Elsevier, 2024)
The limitation of primary and secondary flooding results in more than 60% of original oil in place (OOIP) remains in the reservoir. High interfacial tension (IFT) between crude oil-rock formation as well as oil–water from the primary flooding necessitates the use of IFT reduction agents to suppress this barrier and push the oil to production well. Alkali, surfactant and polymer (ASP) has been utilized in this manner because theoretically it befitting to obtain higher oil recovery during enhanced oil recovery (EOR) process by reducing the IFT and improving the sweep efficiency. Synergism between ASP flooding components outperform the oil recovery limitations and has been successfully demonstrated in numerous field case studies and laboratory results that proves the combination of these chemicals can be more effective than employing them individually. However, while ASP flooding is a positive consequence, it is not without substantial limitations. This paper highlights the success and profound limitations of ASP flooding via its individual and synergistic mechanism with the common type of chemicals that comprise its composition. Towards the end of this paper, owing to the world greener agenda, the feasibility of methyl ester sulfonate (MES) as an alternative green surfactant in this process is also addressed.